2013
DOI: 10.1007/s11274-013-1371-8
|View full text |Cite
|
Sign up to set email alerts
|

Production, purification and characterization of cholesterol oxidase from a newly isolated Streptomyces sp.

Abstract: Cholesterol oxidase production (COD) by a new isolate characterized as Streptomyces sp. was studied in different production media and fermentation conditions. Individual supplementation of 1 % maltose, lactose, sucrose, peptone, soybean meal and yeast extract enhanced COD production by 80-110 % in comparison to the basal production medium (2.4 U/ml). Supplementation of 0.05 % cholesterol (inducer) enhanced COD production by 150 %. COD was purified 14.3-fold and its molecular weight was found to be 62 kDa. Vmax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 35 publications
0
36
1
Order By: Relevance
“…Similar result was reported for the cholesterol oxidase from Streptomyces sp. which was most active at pH 7.0 [35]. The optimum pH of cholesterol oxidase reported from different sources were ranged from 5.0 to 8.5 [10, 21, 22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar result was reported for the cholesterol oxidase from Streptomyces sp. which was most active at pH 7.0 [35]. The optimum pH of cholesterol oxidase reported from different sources were ranged from 5.0 to 8.5 [10, 21, 22].…”
Section: Resultsmentioning
confidence: 99%
“…had an optimum pH for enzyme activity at pH 7.0 and 80% of its activity was retained at pH 6–8 for 24 h, but activity rapidly declined at higher or lower pH, and at pH 10, only 10.16% of its activity was retained [35]. On the other hand, it was found that the optimum pH for the stability of cholesterol oxidase produced by Pseudomonas aeruginosa was pH 6.5.…”
Section: Resultsmentioning
confidence: 99%
“…For the maximum production of CHOx by Streptomyces sp. addition of 0.05% of cholesterol as inducer was found to be most suitable [51]. 0.15% (w/v) cholesterol concentration in the production medium is reported for optimum CHOx production from Rhodococcus sp.…”
Section: Physico-chemical Parameters Affecting Enzyme Productionmentioning
confidence: 94%
“…The Km values were calculated and found to be 428 ± 133 µM (reaction rate) and 350 ± 167 µM (end value) for glucose-hexokinase and 103 ± 39 µM (reaction rate) and 186 ± 49 µM (end value) for cholesterol-cholesterol oxidase respectively. This can be compared with the literature value of 150 µM [38] for hexokinase and 96 µM [39] for cholesterol oxidase. The Km values determined using a CMOS-based device are slightly higher than measured conventionally, this may be due to the pH and/or ionic concentration, which are not optimized for individual reaction but for the two reactions.…”
Section: Simultaneous Detection Of Serum Glucose and Cholesterolmentioning
confidence: 95%